Does surgically assisted maxillary protraction with skeletal anchorage and Class III elastics affect the pharyngeal airway? A retrospective, long-term study - YILMAZ, HANİFE NURAY (My University, 2023)
© 2023 The Korean Association of Orthodontists.Objective: Surgically assisted maxillary protraction is an alternative protocol in severe Class III cases or after the adolescent growth spurt involving increased maxillary advancement. Correction of the maxillary deficiency has been suggested to improve pharyngeal airway dimensions. Therefore, this retrospective study aimed to analyze the airway changes cephalometrically following surgically assisted maxillary protraction with skeletal anchorage and Class III elastics. Methods: The study population consisted of 15 Class III patients treated with surgically assisted maxillary protraction combined with skeletal anchorage and Class III elastics (mean age: 12.9 ± 1.2 years). Growth changes were initially assessed for a mean of 5.5 ± 1.6 months prior to treatment. Airway and skeletal changes in the control (T0), pre-protraction (T1), post-protraction (T2), and follow-up (T3) periods were monitored and compared using lateral cephalometric radiographs. Statistical significance was set at p 0.05). No statistically significant changes were observed in the airway parameters in the follow-up period either. However, Sella to Gonion distance increased significantly (p < 0.05) during the follow-up period. Conclusions: No significant changes in pharyngeal airway parameters were found during the control, maxillary protraction, and follow-up periods. Moreover, the significant increases in the skeletal parameters during maxillary protraction were maintained in the long-term.
Keywords: Tıp; Diş Hekimliği; Sağlık Bilimleri; Medicine; Dentistry; Health Sciences; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; Ortodonti; Orthodontics; Airway; Class III treatment; Maxillary protraction; Surgical assistance